Potential Mediating Role of Polygenic Hazard Score in the Association Between Neurofilament Light Chain and Default Mode Network Connectivity Across the Alzheimer's Disease Continuum - Parsa Saberian; Hamide Nasiri; Fatemeh Kaffashian; Parisa Nasiriansari; Fatemeh Nazari Nasab; Niusha Mehrvarz; Fatemeh Talebizadeh; Shayan Shakeri; Mahsa Mayeli (IBRO Neuroscience Reports)
Background: Alzheimer’s disease (AD) is a complex neurodegenerative disorder marked by progressive cognitive decline and disrupted brain network connectivity, particularly within the default mode network (DMN). Neurofilament light chain (NfL) serves as a biomarker for axonal injury, but the role of genetic predisposition, assessed via the Polygenic Hazard Score (PHS), in mediating the association between plasma NfL and DMN connectivity remains unclear. This study investigates whether PHS mediates the association between plasma NfL levels and DMN connectivity in individuals across different cognitive stages, including cognitively normal (CN), mild cognitive impairment (MCI), and AD. Methods: Data were extracted from the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Plasma NfL concentrations were measured using the Simoa assay, and resting-state fMRI (rs-fMRI), assessed DMN connectivity. The cohort included 102 participants (nCN=28, nMCI=52, and nAD=22). Partial correlation analyses and mediation models were performed, adjusting for age and gender. Statistical significance was set at p < 0.05, after corrections for multiple comparisons. Results: Plasma NfL levels were significantly higher in AD group compared to CN and MCI groups (p = 0.030). DMN connectivity showed substantial declines in the AD group, particularly in the posterior and ventral regions. Significant negative correlations were observed between plasma NfL and ventral DMN connectivity in AD. However, mediation analysis indicated no significant indirect effect of PHS, suggesting that genetic risk does not mediate the plasma NfL-DMN association. Conclusion: These findings suggest that elevated plasma NfL levels are associated with disrupted ventral DMN connectivity in AD, reflecting neurodegeneration-related network dysfunction. However, the lack of a mediating effect by PHS indicates that this relationship is likely independent of genetic risk burden. Clinical Trial Number: not applicable.